Penentuan Nilai Bunga Flat, Efektif, dan Anuitas pada Salah Satu Leasing Motor di Kota Binjai - Dimas Arza Nugraha; Nova Oktavia Sitinjak; Rini Sartika (Lembaga Pengembangan Kinerja Dosen, 2024)
One company that solves financial problems is a motorbike credit company that can help people who are constrained by costs but want to own a motorbike to make their lives easier. One of the motorbike leasing companies that provides a motorbike credit system. One of the products is the Honda ADV 160 ABS which provides various down payment offers with time periods. In this research, the data used is quantitative data in the form of secondary data obtained from motorbike credit brochures on one of the motorbike rentals in the city of Binjai which were registered in October 2023. This research will analyze and compare the results between the total credit interest that matches the flat interest, annuity interest and effective interest which provide slightly lighter installment or credit installment payments. Based on the results obtained from both samples, the lowest total interest is the effective interest.